Is nobody interested in the future of banks? a scoping literature review on the state of the debate - Ulf Hübenbecker (Management Review Quarterly, 2023)
Narratives are playing an increasingly important role in economics since their performative character has been realised. Banks are not unaffected by this, as they face many future challenges and are thus directly affected by narratives. For this reason, this article aims to reveal the future prospects within the academic landscape on the basis of a scoping literature review to create transparency about where the narratives come from. So, it is not the intention to make another prediction about the future of the banks. The paper presents contributions that make explicit statements about the future of banks, either a description of the future or an assessment of the future prospects of banks. Two databases were searched in this context, IDEAS/RePEc and Scopus, for the period from 2001 to 2021. A total of 99 relevant contributions were identified and finally used to answer three questions: (1) What challenges are seen for banks in the future? (2) What kind of future is depicted? (3) How are the future prospects derived? It turns out that challenges are seen in profitability, regulation, technology, and customer behaviour. The future prospects vary considerably, which puts the focus on the last question. Among other things, an overemphasis on intermediation theory tends to generate negative future prospects. It can be seen that the importance of the assumptions for the derivation of future prospects has not yet been recognised and further research is necessary to get a more complete picture of the future of banks.
Keywords: 650; Banks; Future; Narratives; Literature review